Yaśapāla kr̥ta 'Divyā' upanyāsa meṃ strīvāda - Pāṇḍeya, Madhu (Writer on Hindi literature) (Kānapura : Vikāsa Prakāśana, 2019)
A study of the depiction of feminism in Divyā, novel written by Yashpal, 20th century Hindi author.
Includes bibliographical references (pages 102-103).
In Hindi.
Keywords: Yashpal; Feminism in literature; Women in literature; Féminisme dans la littérature.; Femmes dans la littérature.